Obstetric Outcomes and Interventions Between Low Normal Amniotic Fluid Index Compared to True Oligohydramnios [38B]. (May 2017) - Holloman, Conisha; Desai, Neeraj; Paradise, Courtney; Jodicke, Cristiano
Abstract : INTRODUCTION: Our goal was to assess obstetric outcomes and interventions in patients with low normal amniotic fluid index versus oligohydramnios. METHODS: This was a retrospective study of deliveries between 2010 and 2014. Oligohydramnios was defined as Amniotic Fluid Index less than 5 cm (AF-5) and low normal amniotic fluid of 5 to 8 cm (AF-LN) on ultrasound performed greater than 24 hours before delivery. Outcomes included cesarean section, preterm delivery, Apgars at 1 and 5 minutes, umbilical artery pH, birth weight (BW), and admission to neonatal intensive care unit (NICU). Statistics included chi-square and student t-test. RESULTS: 76 cases had AF-5 and 398 had AF-LN. Mean gestational age at delivery was 37.62 and 38.18 weeks (P=.005). Preterm birth rates were higher in AF-5 (P=.003), as well as both primary and all c-section delivery rates (P < .05). Our institution's overall reported primary cesarean section rate for low risk pregnancies was 24%. Neonatal Apgars and BW were significantly lower in AF-5. There was no significant difference in NICU admissions. One fetal death was observed in each group. CONCLUSION: As expected, patients with true oligohydramnios have a higher rate of perinatal morbidity than those with low but normal amniotic fluid, with increased interventions in the true oligohydramnios patients. More investigation is warranted to assess whether earlier intervention in the oligohydramnios group may be the cause of the increased perinatal morbidity.